THE ANALYSIS OF COMMUNITY SATISFACTION INDEX (SMI) ON PUBLIC SERVICES IN SIDOMULYO KELURAHAN OFFICE BENGKULU CITY - Jumagar Lumban Sianta; Karona Cahya Susena; Mimi Kurnia Nengsih (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2020)
The purpose of this study was to determine the Community Satisfaction Index (CSI) in public services in Sidomulyo Urban Village Office of Bengkulu City. The data analysis technique by measuring the value of the Community Satisfaction Index (CSI) based on the Regulation of the Minister of Administrative and Bureaucratic Reform Number 14 Year of 2017. The sample in this study amounted to 370 people in Sidomulyo Urban Village who received services from the Sidomulyo Urban Village Office of Bengkulu City. The cost / tariff element gets the highest rating with an average value of 3.40 with very good evaluation criteria. This illustrates that the community assesses Sidomulyo Urban Village Office of Bengkulu City to provide services free of charge. The lowest satisfaction value is 2.44, which is the completion time with poor evaluation criteria. This illustrates that the time required for the completion of documents is not as promised, due to the slowness of employees in providing services, poor requirements and village heads who are often not available